Oropharyngeal dysphagia management and informed consent: a survey of speech-language pathologists’ practice patterns when recommending modified texture diets - Ward, Matthew G.; Bowman, Angela S. (Frontiers in Rehabilitation Sciences, 2025)
PurposeThe modification of diet textures and liquid viscosity represents the primary form of management of oropharyngeal dysphagia (OD) by speech-language pathologists (SLPs). Despite the ubiquitous use of modified texture diets (MTDs) to prevent aspiration in an attempt to prevent pneumonia, there is no convincing evidence that consumption of MTDs protects individuals with dysphagia from developing pneumonia. Furthermore, informed consent is required for the prescription of MTDs. To date, no study has investigated if practicing SLPs know the risks associated with MTDs, consider the risks when making clinical decisions, and disclose those risks to their patients.MethodThirteen negative health outcomes associated with MTDs were identified in the research literature. A web-based survey was created and distributed. Participants were asked to identify known risks associated with MTDs, how often they considered the risks associated with MTDs before recommending them, and how often they informed patients with OD of the known risks associated with MTDs.ResultsOnly 6.3% of the SLPs surveyed identified all thirteen listed health risks associated with MTDs, and greater than one in five respondents (n = 55; 21.7%) were unable to select even one known risk. Seventy percent (n = 140) of participants indicated that they “almost always” weigh the risks associated with drinking thickened liquids, and fifty-four percent of respondents (n = 108) specified that they “almost always” weigh the risks associated with consuming modified texture solids. Less than half of the participants (n = 99; 49.7%) stated that they “almost always” inform the patient of the risks associated with thickened liquids and 39.9% (n = 79) indicated that they “almost always” inform patients of the risks associated with altered texture solids.ConclusionsParticipants demonstrated poor overall knowledge of the hazards associated with MTDs, limited consideration of known risks of MTDs, and suboptimal levels of disclosure of the risks associated with MTDs to patients with OD.